Addition of H-phosphonates to quinine-derived carbonyl compounds. An unexpected C9 phosphonate–phosphate rearrangement and tandem intramolecular piperidine elimination - Górecki, Łukasz; Mucha, Artur; Kafarski, Paweł (Beilstein Journal of Organic Chemistry, 2014)
The Abramov reaction, a base-catalyzed nucleophilic addition of dialkyl H-phosphonates (phosphites) to carbonyl compounds, was performed with oxidized quinine derivatives as the substrates. Homologous aldehydes obtained from the vinyl group reacted in a typical way which led to α-hydroxyphosphonates, first reported compounds containing a direct P–C bond between the quinine carbon skeleton and a phosphorus atom. For the C9 ketones a phosphonate–phosphate rearrangement, associated with a tandem elimination of the piperidine fragment, was evidenced.
Keywords: carbonyl derivatives; dialkyl phosphite addition; organophosporus; phosphonate–phosphate rearrangement; quinine oxidation